Organización contable en la empresa del Sr. Riofrío Celi Efrén Ubiticio de la ciudad de Loja, periodo del 01 de octubre al 31 de diciembre de 2023 - Balcázar Collaguazo, Jhoselyn Tatiana (2024)
The present Curricular Integration Work called “Accounting organization in the company of Mr. Riofrío Celi Efrén Ubiticio of the city of Loja, period from October 1 to December 31, 2023”, was developed with the purpose of improving the operations of the company, supporting to guarantee an efficient accounting management, a good management of the resources, for the correct decision making, in the financial control and the legal and normative compliance, obtaining a greater competitiveness and sustainability in the market. This work has a mixed approach of exploratory-descriptive type, with the support of research methods and techniques. The fulfillment of the objectives was developed in a chronological manner, starting from the adaptation of the plan and accounts manual to the economic activity of the company; an initial inventory was elaborated through a physical verification, determining the goods, values, obligations and rights, giving way to the elaboration of the Initial Situation Statement. Subsequently, the auxiliary records of purchases, sales, accounts payable and accounts receivable were designed for a better management of the information. Through this compilation, the accounting process was elaborated, recording each of the transactions by means of journal entries applying the permanent account system, which resulted in the preparation of the general ledger, trial balance, work sheet with their respective adjustments, finally obtaining the Financial Statements, where it is reflected that the company obtained a net profit of $12,039.04. At the end of the curricular integration work, the appropriate conclusions and recommendations are emphasized, where it is intended that the owner puts into practice since the processes and techniques applied allow to have a better control and management of the resources for the economic-financial growth of the company.